MENGKAJI KLONING MANUSIA DARI PERSPEKTIF HUKUM KODRAT - Fadri, Zainal (JURNAL AL-AQIDAH, 2020)
Cloning has become a hot topic since technology activists in the field of genetics explained the results of their research that the reproductive process can occur with the help of technology. People have taken advantage of the results of this technology, although the debate about its use in humans is still not a comprehensive concept. This study aims to assess the extent to which the human cloning program is viewed from natural law, considering that cloning is an activity to bring back humans who have died. The method used in this research is literature review with a holistic analysis of the natural law view of human cloning. The results of this research indicate that the human cloning program is returned to the beneficiaries of this program and is fully responsible for the decisions taken